Dance Composition Music Urip Ing Geni | Komposisi Musik Tari Urip Ing Geni - Wayan Dodi Setiawan (GHURNITA: Jurnal Seni Karawitan, 2023)
The work of the dance music "Urip Ing Geni" was realized because of the importance of the role of fire or Agni in the lives of Hindus. Inspired by everyday life in Hindu religious ceremonies, fire has a very important function and role. In the composition of karawitan dance music this is using the media revealed gamelan gong kebyar, with this structure divided into three parts, namely kawitan, pangawak, and pangecet. In the form of innovative works with a melodic and rhythmic work approach. This work was created with the approval of MBKM partner Sanggar Puja Saraswati in Rejobinangun village. The importance of the role of dance is meant to support the ritual procession, namely the dance, especially in East Lampung. The formulation of this idea of creation is 1) how the form and structure of Urip Ing Geni dance music, 2) how the process of creation of Urip Ing Geni dance music work, 3) why it is important for this dance to be created, with the formulation of the creator's idea, , so the purpose of the creation of this work is 1) describing the shape and structure of urip Ing Geni dance music, 2) comprehensively describes the process of creating urip Ing Geni dance music, 3) outlining the importance of Urip Ing Geni dance music is created. While the method used refers to the stage of dance creation, namely the stage of exploration, improvisation, and formation.